(untitled) (Eurasian Medical Research Periodical, 2022)
Assessment of physical development (PD) is an integral component in the study of the health status of the child population due to the fact that it clearly reflects the influence of environmental factors, lifestyle and the educational process on the body. Assessment of physical development includes a set of indicators: somatometric, somatoscopic and physiometric, among which the most commonly used for assessment are the following: body length and weight, chest circumference.